PURIFIKASI DAN MODERNISASI DI MUHAMMADIYAH RANTING ULUJAMI JAKARTA SELATAN - AI FATIMAH NUR FUAD (Universitas Muhammadiyah Prof Dr Hamka, 2018)
This research studied on purification and modernization of Muhammadiyah in the Ranting Ulujami, South Jakarta. This research is conducted through qualitative method combining three data collection techniques; review on documents (books and journal articles), interview, and observation. This research reveals that purification and modernization as the main character of Muhammadiyah, are performed by its branch in the Ranting Ulujami. Regarding the purification of aspect of worship (mahdhoh), the Muhammadiyah leaders in the Ranting emphasize the need to strongly hold the hadith shohih and reject the hadith dhoif. Innovation in worship, for these leaders, is bid'ah. However, the implementation of the purification has been negotiated with the local religious tradition that has been long established in Ulujami. Tahlilan, a religious ceremony during the death of family, is an example. The Muhammadiyah in Ulujami negotiate it by producing new kind of tahlilan, or constructing new meaning of the tahlilan to prevent them from